2021
DOI: 10.1186/s40066-021-00304-x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for food security and safety: a qualitative study in an agriculture supply chain company in Iran

Abstract: Background Food supply chain companies are major link for safe food production and distribution. Food safety ensures reduced food losses and, therefore, contributes to food security. Although there have been extensive studies on the food industry with different perspectives, no study has so far been conducted on the challenges in terms of the food security. The present study is a qualitative one conducted in 2019 in one of the largest agricultural production chain companies in Khorasan Razavi p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The performance analysis of supply chain actors is calculated using the DEA method with the assumption of output-oriented CRS (Sadati, Nayedar, Zartash, & Falakodin, 2021;Hung & Khai, 2020). That is, how much output must be produced using the same amount of input, so that the DMU becomes efficient.…”
Section: Supply Chain Institutional Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The performance analysis of supply chain actors is calculated using the DEA method with the assumption of output-oriented CRS (Sadati, Nayedar, Zartash, & Falakodin, 2021;Hung & Khai, 2020). That is, how much output must be produced using the same amount of input, so that the DMU becomes efficient.…”
Section: Supply Chain Institutional Performancementioning
confidence: 99%
“…The current increase in animal feed prices is influenced by the price considering that corn used for animal feed must be imported and accounts for almost 70% of the cost of making animal feed. This condition is burdensome for smallholder farmers and will eventually affect buyers, especially the price of chicken meat and eggs (Kamble, Gunasekaran, & Gawankar, 2020;Ilyas et al, 2020;Sharma, Kamble, Gunasekaran, Kumar, & Kumar, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Meysenburg et al (2014) have also reported that despite the acceptable knowledge, attitude, and practices of producers and consumers expressed in their study, a number of researches have also revealed unacceptable food handling habits among key players in the food value chain (Cramer, 2022; Kiss, 2020; Sadati et al, 2021). Consumers may be exposed to a range of potential dietary dangers through their eating patterns and food preferences (Miles et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Insufficient knowledge of food safety issues could be a barrier that can prevent consumers from changing risk behaviors (Angelillo et al, 2001). Furthermore, Meysenburg et al (2014) have also reported that despite the acceptable knowledge, attitude, and practices of producers and consumers expressed in their study, a number of researches have also revealed unacceptable food handling habits among key players in the food value chain (Cramer, 2022;Kiss, 2020;Sadati et al, 2021).…”
mentioning
confidence: 99%
“…The agricultural sector has the potential to be the industrial and economic platform from which the speedy development of a country can take off as Nigeria faces huge food security challenges (Olarinde and Abdullahi 2014). According to Sadati et al (2021), the poor performance of the agricultural sector and associated food insecurity could be due to a myriad of factors including economic policy and its uncertainty (Olarinde and Abdullahi 2014). Economic policy uncertainty occurs when an economic body cannot predict exactly whether, when, and how the government will change its current economic policy (Guo et al 2020).…”
Section: Introductionmentioning
confidence: 99%